2008
DOI: 10.1152/ajpheart.00935.2007
|View full text |Cite
|
Sign up to set email alerts
|

In vivo genetic profiling and cellular localization of apelin reveals a hypoxia-sensitive, endothelial-centered pathway activated in ischemic heart failure

Abstract: Quertermous T. In vivo genetic profiling and cellular localization of apelin reveals a hypoxia-sensitive, endothelial-centered pathway activated in ischemic heart failure. Am J Physiol Heart Circ Physiol 294: H88-H98, 2008. First published September 28, 2007 doi:10.1152/ajpheart.00935.2007.-Signaling by the peptide ligand apelin and its cognate G protein-coupled receptor APJ has a potent inotropic effect on cardiac contractility and modulates systemic vascular resistance through nitric oxide-dependent signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
126
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(136 citation statements)
references
References 38 publications
9
126
1
Order By: Relevance
“…Hypoxia-induced myocardial/endothelial apelin expression has been demonstrated via hypoxia-inducible factor (HIF) pathways (Glassford et al 2007, Ronkainen et al 2007, and the HIF-1 pathway is activated in patients with OSA (Atkeson & Jelic 2008). The pulmonary apelin-producing endothelium is particularly sensitive to hypoxia (Sheikh et al 2008). Thus, upregulation of apelin in OSA may be a protective mechanism against OSA-associated hypertension and recurrent hypoxia/hypoxaemia, and endothelial dysfunction may represent the dominant mechanism for circulating plasma apelin levels in this patient group.…”
Section: Discussionmentioning
confidence: 98%
“…Hypoxia-induced myocardial/endothelial apelin expression has been demonstrated via hypoxia-inducible factor (HIF) pathways (Glassford et al 2007, Ronkainen et al 2007, and the HIF-1 pathway is activated in patients with OSA (Atkeson & Jelic 2008). The pulmonary apelin-producing endothelium is particularly sensitive to hypoxia (Sheikh et al 2008). Thus, upregulation of apelin in OSA may be a protective mechanism against OSA-associated hypertension and recurrent hypoxia/hypoxaemia, and endothelial dysfunction may represent the dominant mechanism for circulating plasma apelin levels in this patient group.…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, for most of the HKG used in published results, no exhaustive studies of their variations in dedicated conditions have been performed yet. For example, a lot of reports deal with transcripts variation under hypoxia (Helczynska et al, 2008;Seifeddine et al, 2008;Sheikh et al, 2008;Chaudary and Hill, 2009;Zhang et al, 2009). Authors formulate relevant conclusions regarding gene expression on the basis of the use in most cases of a unique or more rarely a specific set of HKG.…”
Section: Discussionmentioning
confidence: 99%
“…Many publications dealing with cancer have reported gene expression studies in hypoxic conditions (Helczynska et al, 2008;Seifeddine et al, 2008;Sheikh et al, 2008;Chaudary and Hill, 2009;Zhang et al, 2009), but until now related HKG variations have not yet been much characterised (Zhong and Simons, 1999). However, analysing if HKG expression is stable under different oxygen concentrations remains an important issue especially in cancer field as it is well known that proliferating tumours often grow in hypoxic conditions (Semenza, 2003).…”
mentioning
confidence: 99%
“…However, studying the racemic status 23 was the determinant for decreased plasma apelin content among heart involvement. In contrast, the recent studies reported by Sheikh and associates 24 demonstrated that apelin and APJ were up-regulated in the heart and skeletal muscle after myocardial injury, suggesting that apelin expression remains in the endothelium.…”
Section: Discussionmentioning
confidence: 61%
“…Studies suggest that apelin-expressing endothelial cells respond in conditions associated with heart failure, possibly including local tissue hypoxia, thereby modulating apelin-APJ expression to regulate cardiovascular homeostasis, the apelin-APJ pathway may thus provide a mechanism for systemic endothelial monitoring of tissue perfusion and adaptive regulation of cardiovascular function. 24 Because apelin improves glucose uptake and mediates the inflammatory response, apelin may be a promising therapeutic agent for type 2 diabetes. However, further studies that investigate the protein and mRNA levels of the anti-insulin resistant effect of apelin, and in vivo studies of apelin in insulinresistant animals are necessary to elucidate its pharmaceutical potential.…”
Section: Discussionmentioning
confidence: 99%